TEMPERATURE AND HUMIDITY AFFECT POLLEN VIABILITY AND MAY TRIGGER DISTYLY DISRUPTION IN THREATENED SPECIES - Aronne, G.; Iovane, M.; Strumia, S. (Annali di Botanica, 2020)
Within the ongoing trend of rapid climate changes there is an urgent need to assess the vulnerability of the endangered species for evaluating their conservation status and planning effective actions. Primula palinuri Petagna is a relict chasmophyte classified as Vulnerable due to its decreasing populations. The species evolved a distylous syndrome: a reproductive system that maintains a high genetic variability by enhancing cross-pollination. Using an experimental approach, we compared the effect of three different temperatures and three levels of relative humidity on pollen viability of both short-styled and long styled flowers of P. palinuri. Data highlighted that temperature and humidity significantly affect pollen viability. Notably, pollen of short-styled flowers showed a significant higher viability than the long-styled morph in any of the tested treatments. Such results raised the concern for distyly equilibrium disruption in this species, a phenomenon that in isolated populations may cause a sharp raising of the risk of local extinction. Overall, results on this Primula species suggest that in a scenario of climate changes the effect of environmental factors on pollen functionality of any endangered distylous species should not be overlooked for their vulnerability assessment and conservation status evaluation.